2017
DOI: 10.1021/acs.iecr.7b02343
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Investigation and Comparison of Absorption Cycles Using Hydrofluoroolefins and Ionic Liquid

Abstract: To overcome the problems of conventional absorption working fluids, the novel hydrofluoroolefins (HFOs) and ionic liquid (IL) were analyzed. The refrigerants were 2,3,3,3-tetrafluoropropylene (R1234yf) and trans-1,3,3,3tetrafluoropropene (R1234ze(E)), and the absorbent was 1hexyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide ([hmim][Tf 2 N]). The property models of HFO/IL and the thermodynamic models of absorption cycles were built with verified accuracy. Analyses show that the coefficient of performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…According to the working practice of absorption refrigeration or heat pump system, the cycle process of the working pairs mainly involves the transport, heat, and mass transfer and other physical processes, which are closely related to the density, viscosity, surface tension, and other basic physical properties of working pairs. So far, many research groups have carried out studies on the basic physical and chemical properties of binary or ternary systems composed of ionic liquids and other substances. Królikowska et al synthesized four bromide-based ILs of [C 1 C 2 PIP]­Br, [C 1 C 4 PIP]­Br, [C 4 Py]­Br, and [N 2,2,2,4 ]Br and obtained the density, viscosity, and phase equilibrium data of their aqueous solutions with a differential scanning microcalorimetry technique. On the basis of experimental density data, the apparent molar volumes, limiting apparent molar volumes, limiting molar expansibilities, and isobaric thermal expansion coefficients were obtained.…”
Section: Introductionmentioning
confidence: 99%
“…According to the working practice of absorption refrigeration or heat pump system, the cycle process of the working pairs mainly involves the transport, heat, and mass transfer and other physical processes, which are closely related to the density, viscosity, surface tension, and other basic physical properties of working pairs. So far, many research groups have carried out studies on the basic physical and chemical properties of binary or ternary systems composed of ionic liquids and other substances. Królikowska et al synthesized four bromide-based ILs of [C 1 C 2 PIP]­Br, [C 1 C 4 PIP]­Br, [C 4 Py]­Br, and [N 2,2,2,4 ]Br and obtained the density, viscosity, and phase equilibrium data of their aqueous solutions with a differential scanning microcalorimetry technique. On the basis of experimental density data, the apparent molar volumes, limiting apparent molar volumes, limiting molar expansibilities, and isobaric thermal expansion coefficients were obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Kim and Kohl investigated the performance of R134a/[hmim]­[PF 6 ] and R134a/[hmim]­[Tf 2 N], showing that R134a/[hmim]­[Tf 2 N] has a maximum COP of about 0.5, while R134a/[hmim]­[PF 6 ] is about 0.2. Wu et al analyzed the COPs and ECOPs of [hmim]­[Tf 2 N] with R1234yf and R1234ze­(E), and found that their COPs are much lower than those of H 2 O/LiBr and NH 3 /H 2 O. Sujatha and Venkatarathnam compared the cooling performance of vapor–absorption cycles using R1234yf, R1234ze­(E), R125, R152a, or R32 as a refrigerant and [hmim]­[Tf 2 N] as an absorbent. Small equipment volume is needed using R32/[hmim]­[Tf 2 N] and R152a/[hmim]­[Tf 2 N] pairs owing to the evaporation pressure, particularly the pressure for R32/[hmim]­[Tf 2 N] is about 2 orders of magnitude higher than that in H 2 O/LiBr systems.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the powder catalysts are coated on ceramic monolith supports to achieve low pressure drop and high surface‐to‐volume ratio, [ 16–18 ] the obvious drawbacks of ceramic support suffers from the poor inter‐phase heat transfer ability, the high brittleness and the random distribution of catalyst powders on the edge are still unavoidable. [ 19,20 ] In addition, the poor substrate adhesion will also cause the peeling off of active Co 3 O 4 /TiO 2 catalysts and subsequent catalytic performance reduction. Therefore, it is technologically important to develop some innovative solution to anchor TiO 2 support on flexible substrate.…”
Section: Introductionmentioning
confidence: 99%